1999
DOI: 10.1246/cl.1999.1037
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Carbon Hexagonal Plane by Ligand Exchange Reaction of Ferrocene

Abstract: Introduction of the functional groups to the carbon hexagonal plane of the sp2-carbon, which may provide the novel properties to carbon materials, proceeds by the ligand exchange reaction of ferrocene with the sp2-carbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Grafting of polymers onto GO by ligand-exchange reaction with ferrocene 3.1. Ligand-exchange reaction of ferrocene with graphene structure of nanocarbons Morrison et al reported that the h 6 -benzene-h 5 -cyclopentadienyliron cation could be readily prepared by the ligand-exchange reaction of ferrocene with benzene in the presence of AlCl 3 and Al powders as the catalysts [31,32]. Furthermore, Miyake et al reported that the ligand-exchange reaction is successfully applied for the introduction of functional groups to graphene structure of various carbon materials [32].…”
Section: Identification Of Peg Grafting Onto Go By Gc-msmentioning
confidence: 99%
“…Grafting of polymers onto GO by ligand-exchange reaction with ferrocene 3.1. Ligand-exchange reaction of ferrocene with graphene structure of nanocarbons Morrison et al reported that the h 6 -benzene-h 5 -cyclopentadienyliron cation could be readily prepared by the ligand-exchange reaction of ferrocene with benzene in the presence of AlCl 3 and Al powders as the catalysts [31,32]. Furthermore, Miyake et al reported that the ligand-exchange reaction is successfully applied for the introduction of functional groups to graphene structure of various carbon materials [32].…”
Section: Identification Of Peg Grafting Onto Go By Gc-msmentioning
confidence: 99%
“…In the coexistence of AlCl 3 and Al powder, poly(Vf-co-MMA) was successfully grafted onto ND surfaces (Run 4). It is because AlCl 3 receives cyclopentadiene of ferrocene, and after the grafting of the copolymers, iron in ferrocene moiety exists in reduced form [24], because it is known that Al powder prevents ferrocene from being oxidized to ferricinium cation [25].…”
Section: Grafting Of Poly(vf-co-vinyl Monomer) Onto Ndsmentioning
confidence: 99%
“…The results indicate that the ligand-exchange reaction of ferrocene containing polymer with ND needs large excess of catalyst. In general, the ligand-exchange reaction of ferrocene with carbon black carried out in the presence of a large excess of AlCl 3 [24,25]. This may be due to deactivation of catalysts by the interaction with functional groups on ND surface.…”
Section: Grafting Of Poly(vf-co-vinyl Monomer) Onto Ndsmentioning
confidence: 99%
“…[41][42][43][44] Miyake et al reported that ligandexchange reaction of ferrocene can be applied to the introduction of functional groups to graphene sheet of various carbon materials, such as active carbon fiber and carbon black. 45 Grafting of Poly(Vf-co-MMA) onto CNT and VGCF…”
Section: Grafting Of Polymers Onto Carbon Nanotube and Nanofiber Surfmentioning
confidence: 99%